Fuel Feeder of Screw Type for Biomass Fuel - Suprapta Winaya, I Nyoman; Ardhikayana, I B; Ngrh.Pt. Tenaya, I Gst. (Jurnal Energi Dan Manufaktur, 2012)
Fuel Feeder of Screw Type for Biomass Fuel
Keywords: Biomass, Screwed fuel feeder, Feeding rate